PERANCANGAN MOCKUP USER INTERFACE (UI) BERDASARKAN USER EXPERIENCE (UX) APLIKASI BELAJAR BAHASA ARAB MENGGUNAKAN METODE USER CENTERED DESIGN - Egia Rosi Subhiyakto; Dian Indah Fajriati (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2021)
Arabic and not cause children to get bored or bored quickly when learning. Therefore, it is necessary to design a User interface Mockup based on User experience analysis of Arabic learning applications that focus on children using the User-Centered Design (UCD) method. This method has four stages, namely introduction of user characteristics, collection and alignment of designs, design solutions, and testing of design solutions. The results obtained in the child persona trial as the main subject have an average value of 82 and the results of the parental persona trial as a supporting subject have an average value of 81.16 while the Usability test results obtained a value of 85.46%. And then the design solution that has been made can be categorized as acceptable with grade A and an adjective rating of Excellent based on the System Usability Scale and can be used as a UI/UX design recommendation for the Children's Arabic Learning Application.